ANALYZING THE CUSTOMER DECISION MAKING ON USING KARTU HALO TELKOMSEL IN MANADO BASED ON PSYCHOGRAPHIC SEGMENTATION - Rarung, Prischa (Sam Ratulangi University, 2016)
The new inventions in communication technology caused the industries development in telecommunication aspect grows rapidly. Telkomsel is a telecommunication service company that runs in GSM (Global System for Mobile Communication) basis which offer some kind of cellular cards to the consumers. This research is conduct in Manado, North Sulawesi. The objectives of this research are to analyze the customer decision making on using Kartu Halo based on psychographic segmentations, partially and simultaneously. This research is the causal type of research where it will investigate the influence of factors towards decision making on using Kartu Halo. Use multiple regression models to answer the research problem. The population in this study is a consumers of Kartu Halo, whereas samples taken by each respondent 100 respondents. The hypothesis testing, this research conduct a conclusion of there is a significant influence of Attitude, Value and Lifestyle simultaneously and there is a significant influence of Lifestyle partially on customer decision making on using Kartu Halo. This study reveals that customers lifestyle has a strong influence factors in order to use Kartu Halo.